2009
DOI: 10.1007/s10384-009-0678-3
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid-associated optic neuropathy in a patient with ocular sarcoidosis

Abstract: Our findings demonstrate that it is important for ophthalmologists as well as physicians and orthopedists to consider the possibility of optic neuropathy caused by long-term use of linezolid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Eighteen patients across twelve case reports were reviewed and data was collected on linezolid dose and length of treatment as well as time to visual recovery. 1 , 2 , 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Recovery was typically described in case reports as an improvement in visual function to an acceptable level, usually assessed by visual acuity, visual fields, color vision or improvement in OCT-RNFL edema. It was not uncommon to have evidence of permanent damage, despite subjective return of visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen patients across twelve case reports were reviewed and data was collected on linezolid dose and length of treatment as well as time to visual recovery. 1 , 2 , 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Recovery was typically described in case reports as an improvement in visual function to an acceptable level, usually assessed by visual acuity, visual fields, color vision or improvement in OCT-RNFL edema. It was not uncommon to have evidence of permanent damage, despite subjective return of visual function.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports describing the use of steroid pulse therapy for sarcoidosis, including cardiac sarcoidosis [12,13], neurosarcoidosis [14], and pulmonary sarcoidosis [15,16]. With respect to ocular sarcoidosis, a few previous reports described the use of steroid pulse therapy for panuveitis [17] or optic neuropathy [18], yet to the best of our knowledge, there are no previously published reports on choroidal granuloma. However, Knickelbein et al [19] reported a refractory patient with a large choroidal granuloma, panuveitis, and optic disc edema being treated with high-dose intravenous steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Data from [5,9–11,15–23,32,34,39 ▪ ,40 ▪ ,41–57,58 ▪ ,59–66]. MRSA, methicillin-resistant staphylococcus aureus; TB, tuberculosis.…”
Section: Characteristics Of Linezolid-associated Optic Neuropathymentioning
confidence: 99%